(untitled) (Herald of Journalism, 2023)
In the previous issue of our scientific journal (Herald of KazNU, Journalism Series, No. 2 (68) 2023, pp. 16-28) the translation from English of the first part of Sarah Oates’s program article “The Neo-Soviet Media Model,” published in 2007 in the journal “Europe-Asia Studies” (Sarah Oates, 2007) was first presented to the readers. Also the “Foreword by the scientific editor of the translation, professor of National Research University “Higher School of Economics” in Moscow, S.G. Davydov was published. It contained deeper scientific understanding and a critical view at methodology of the research, as well as the theoretical and historical contexts of scientific discussions about normative media theories of the 2000s. In the current issue, readers are offered the translation of the second (final) part of Sarah Oates’s article, in which, according to the author’s annotation, “explores the genesis of the neo-Soviet media model. Based on the results of the study of Russian media in the post-Soviet period, as well as a review of their activities during elections in the above region, the article concludes that Russian media currently operate in a “neo-Soviet” manner. Factors shaping this media model include the rejection of a balanced approach or objectivity; the presence of flaws in the legislation regulating the activities of the media; self-censorship; state interference and pressure on the media; lack of professionalism in the journalistic environment; and an atmosphere of violence against journalists. Furthermore, in the transition from the Soviet to the neo-Soviet model, there is continuity in how the media are perceived by their audience.”